Perspectives, Knowledge, and Fears of Cancer Patients About COVID-19 - Guven, Deniz Can; Sahin, Taha Koray; Aktepe, Oktay Halit; Yildirim, Hasan Cagri; Aksoy, Sercan; Kilickap, Saadettin (Frontiers in Oncology, 2020)
The COVID-19 expected to significantly affect the cancer patients due to adverse outcomes with COVID-19 and disruptions in cancer care. Another important point is the stress and anxiety burden of COVID-19, which could affect the quality of life. Patient education is vital due to the vulnerability of the topic to disinformation. To determine the areas needing improvements in patient education, and coping with stress, the burden of the problem should be pictured. From this point, we aimed to assess the perspectives and fears of cancer patients about COVID-19 with resources of COVID-19 knowledge with a questionnaire. A total of 250 adult cancer patients applied to the outpatient chemotherapy unit of Hacettepe University Cancer Center between the 27.05.2020 and 09.06.2020 invited to a questionnaire of 13 multiple choice questions with a return rate of 78% (195/250). Most patients acquired their knowledge about COVID-19 from television (91.9%). Social media was the second most common source of knowledge (43.8%) with a prediction in younger patients, non-smokers, targeted therapy or immunotherapy treated patients, and breast cancer patients (>65 vs. <65 years of age, p=0.057; non-smoker vs. ever-smoker, p=0.036; targeted therapy and immunotherapy vs. chemotherapy, p=0.004; breast cancer vs. other cancers, p=0.019). The percentage of patients seeing the information about COVID-19 as adequate (38.9%) or inadequate (35.1%) was similar. More than 90% of the patients had a moderate to severe degree of COVID-19 fear. 27.6% of patients had the false knowledge of glove using as a protective measure for COVID-19. More than half of the patients had another wrong knowledge as the need for the supplements for COVID-19 protection. A significant percentage of patients (84.7%) expected some level of disruption in oncological care with the expectation of a moderate-to-severe disruption was more common in the advanced stage patients (p=0.026). In our experience, most cancer patients had a significant degree of fear about both infecting COVID-19 and the disruption of cancer care by COVID-19. A significant amount of our patients had the wrong information about the protection necessities, which denotes the need for better patient education about COVID-19.